ANALYSIS OF THE CONSTITUTIONAL COURT’S DECISION REGARDING THE AGE LIMIT FOR PRESIDENTIAL AND VICE-PRESIDENTIAL CANDIDATES - Arlen Citra Narindra; Fathimah Natia Salsabila; Nazwa Ayuni; Rayyan Muhammad Aulia (Problematika Hukum, 2020)
The constitutional court or commonly abbreviated (MK) is the guardian of the constitution in the scope of Indonesian state administration. In this case the constitutional court is tasked with reviving the constitution and enforcing it if there are violations that occur. Indiscriminately and remain straight on the existing codification. However, recently, the Constitutional Court was shaken by an extraordinary new problem that had never been experienced before. The impact of this case finally dragged the chief judge Anwar Usman down from his position. This research will discuss the problem of the decision handed down by the Constitutional Court on the judicial review of Law Number 7 of 2017 concerning General Elections in determining the minimum age limit for the president which finally dragged the Chief Justice of the Constitutional Court for violating ethics and allegations of nepotism.Keywords: Constitutional Court; President; age limit; nepotism; ethics